KAJIAN AIR PANTAI WONG POLO MENUJU DESA WISATA DESA KOTA PARI - Rahmadhani Fitri; Hanifah Mutia Z.N. Amrul (Universitas Pahlawan Tuanku Tambusai, 2022)
Kota Pari Village is a village located in Pantai Cermin sub-district, Serdang Bedagai district, North Sumatra province. Kota Pari Village has beach tourism that is not yet known to the public, namely mangrove tourism, Wong Polo Beach and Dua Rasa Beach. This coastal tourism potential will attract visitors if it is planned in accordance with the safety and comfort of visitors without damaging the ecology. Pari Village Tourism Planning This is done by analyzing the water pollution index which has been determined by the Minister of Environment Decree No. 51 of 2004 Seawater Quality Standards are parameters of TDS, salinity, pH and BOD. The selection of parameters is analyzed based on the needs of the beach for the convenience of the community. Based on the results of the analysis and research data, it can be seen that the results of the quality standards of wong Polo beach water have several contaminants that are taken into consideration in the planning of wong Polo marine tourism. Marine tourism planning can be planned as an aesthetic for visitors who come and can enjoy the view of wong polo beach marine tourism. Keywords: Kota Pari Village, Wong Polo Beach, Marine Tourism